National Policy on Particularly Sensitive Sea Ares: Step Towards Indonesian Marine Protection and Sustainable Shipping - Hartanto, Dhimas Rudy (Jurnal Lemhannas RI, 2024)
Purpose: This study examines Indonesia’s challenges in protecting its marine environment due to intensive shipping activities in high-traffic maritime routes. It evaluates the alignment of Indonesian regulations with international standards, focusing on the Particularly Sensitive Sea Areas (PSSA) framework under IMO Resolution A.982(24). Study Design/Methodology/Approach: The research employs a qualitative legal-normative approach to analyze Indonesia’s regulatory framework in comparison with international maritime conservation standards. It assesses national policies, including Law Number 32 of 2009 on Environmental Protection and Management and Law Number 17 of 2008 on Shipping, identifying regulatory gaps, institutional limitations, and coordination challenges that hinder effective PSSA implementation. Findings: The study finds that Indonesia’s existing regulations lack specific provisions to implement PSSA standards effectively, leading to weak enforcement and ineffective marine protection. Additionally, poor inter-agency coordination, limited institutional capacity, and low stakeholder awareness hinder sustainable maritime conservation efforts. The absence of advanced environmental monitoring technologies and public engagement strategies further reduces marine ecosystem resilience. Originality/Value: This research provides a critical legal analysis of Indonesia’s PSSA-related policies, offering practical recommendations for regulatory improvement. By proposing revisions to national laws, strengthening inter-agency coordination, integrating advanced maritime monitoring technologies, and increasing public awareness, this study contributes valuable insights for policymakers, maritime authorities, and environmental advocates. The findings support Indonesia’s compliance with international obligations, ensuring long-term marine resource preservation and sustainable maritime development.